Critical analysis of spirometric patterns in correlation to chest computed tomography among adult Indigenous Australians with chronic airway diseases. (2nd September 2021) - Heraganahally, Subash S; Howarth, Timothy; Mo, Lin; Sorger, Lisa; Ben Saad, Helmi
ABSTRACT: Background : There is sparse literature evidence in the spirometric patterns of adult Indigenous Australians with and without chest computed tomography (CT)-proven chronic airway diseases (CADs).Methods : Participants spirometry testing graded as acceptable for quality and had a chest CT scan showing radiographic evidence of CADs were included for analysis.Results : Of the 1350 spirometric tests performed between 2012 and 2020, a total of 212 patients with a mean age of 53 years and 54% females were eligible to be included. One-third (30%) had normal chest CT (without CADs), 35% had predominant COPD, 19% bronchiectasis and 16% combined COPD and bronchiectasis. Percentage predicted values for forced vital capacity (FVC) and forced expiratory volume in one second (FEV1 ) both pre- and post- bronchodilator were significantly reduced for all participants – FVC: CT-normal 64%, 65%; COPD 58%, 62%; bronchiectasis 54%, 54%; combined COPD and bronchiectasis 50%, 53%. FEV1 : CT-normal 62%, 65%; COPD 46%, 49%; bronchiectasis 48%, 51%; combined COPD and bronchiectasis 36%, 40%. FEV1 /FVC was only reduced for CT abnormality patients – CT-normal 96%, 98%; COPD 77%, 77%; bronchiectasis 87%, 89%; combined COPD and bronchiectasis 71%, 72%.Conclusions : Restrictive spirometric pattern is common and an obstructive pattern with COPD, in isolation or when COPD coexists with bronchiectasis.